2015
DOI: 10.1002/jcop.21708
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Ethnic Density Effects, Acculturation, and Adjustment: The Case of Russian-Speaking Immigrants From the Former Soviet Union

Abstract: There has been limited advancement in the empirical literature unpacking the ethnic density effect, a social ecological phenomenon that may help explain some of the conflicting findings in bidimensional acculturation research. In this study, we developed a brief measure of perceived ethnic density in a community sample of in Montreal, Canada, finding it to be a superior predictor of distress to objective linguistic density. Acquiring social support partly mediated the relation between perceived ethnic density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 45 publications
(116 reference statements)
3
23
0
Order By: Relevance
“…Birman et al (2005) and Miller and colleagues (2009) both also found a positive association in the United States, but they relied on an objective, census-based measure of ethnic density. In contrast, Jurcik and colleagues (Jurcik et al, 2015;Jurcik et al, 2013) used a subjective measure of ethnic density and did not detect any association with heritage acculturation in Canada (although their subjective measure correlated with an objective indicator of ethnic density). Instead, they found that subjective perceptions of ethnic density interacted with heritage acculturation in the prediction of psychological adjustment.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Birman et al (2005) and Miller and colleagues (2009) both also found a positive association in the United States, but they relied on an objective, census-based measure of ethnic density. In contrast, Jurcik and colleagues (Jurcik et al, 2015;Jurcik et al, 2013) used a subjective measure of ethnic density and did not detect any association with heritage acculturation in Canada (although their subjective measure correlated with an objective indicator of ethnic density). Instead, they found that subjective perceptions of ethnic density interacted with heritage acculturation in the prediction of psychological adjustment.…”
Section: Discussionmentioning
confidence: 89%
“…A third question, also identified by Schachner and colleagues (2017; and discussed by Jurcik et al, 2015), concerns interactions among contexts at different levels. Considering the acculturating person in context as a single multilevel dynamic system (Ryder et al, 2011) suggests that contextual factors may not act in a simply additive fashion.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Language proficiency, acculturation, health beliefs, prior experiences, and cultural norms are important factors related to health literacy and health outcomes in immigrants in general as well as in FSU immigrants [ 44 , 45 , 61 , 76 , 77 ]. In addition, FSU immigrants may experience difficulties associated with relocation and acculturation, despite high educational attainment and similarity among the racial majority of many settings [ 69 , 78 , 79 , 80 , 81 ]. For instance, even after controlling for education and other demographic factors, middle-aged FSU immigrant women in Israel were significantly less likely to be knowledgeable about heart disease than long-term Israeli Jews [ 82 ].…”
Section: Resultsmentioning
confidence: 99%